PENINGKATAN LITERASI LINGKUNGAN SISWA MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Lana, Yusro; Hadi, Wiwin Puspita; Wahyuni, Eva Ari; Putera, Dwi Bagus Rendy Astid; Fikriyah, Aida (Natural Science Education Research, 2025)
The purpose of this study was to determine the increase in environmental literacy after the implementation of the STM-assisted problem based learning model. At SMP Negeri 3 Burneh, Bangkalan Regency. This study uses the Problem Based Learning learning. The population of this study were all grade VII students in the 2023/2024 Academic Year. Sampling used a saturated sampling technique. The research sample was 28 students. Data were collected using environmental literacy questions, student response questionnaires, and learning implementation observation sheets. The results showed that: 1) the free sample T test obtained an α result of 0.003, namely there was a difference between the experimental and control groups in the posttest. 2) The N-Gain Score result in the experimental group was 0.3 with a moderate category